Biogeography of the fish pathogen Aeromonas salmonicida inferred by vapA genotyping. Issue 7 (12th April 2019) - Gulla, Snorre; Bayliss, Sion; Björnsdóttir, Bryndís; Dalsgaard, Inger; Haenen, Olga; Jansson, Eva; McCarthy, Una; Scholz, Felix; Vercauteren, Maaike; Verner-Jeffreys, David; Welch, Tim; Wiklund, Tom; et al.
ABSTRACT: A recently described typing system based on sequence variation in the virulence array protein ( vapA ) gene, encoding the A-layer surface protein array, allows unambiguous subtyping of Aeromonas salmonicida . In the present study, we compile A-layer typing results from a total of 675 A. salmonicida isolates, recovered over a 59-year period from 50 different fish species in 26 countries. Nine novel A-layer types (15–23) are identified, several of which display a strong predilection towards certain fish hosts, including e.g. Cyprinidae and Pleuronectidae species. Moreover, we find indications that anthropogenic transport of live fish may have aided the near global dissemination of two cyprinid-associated A-layer types. Comparison of whole genome phylogeny and A-layer typing for a subset of strains further resulted in compatible tree topologies, indicating the utility of vapA as a phylogenetic as well as an epizootiological marker in A. salmonicida . A Microreact project (microreact.org/project/r1pcOAx9m ) has been created, allowing public access to the vapA analyses and relevant metadata. In sum, the results generated provide valuable insights into the global population structure of A. salmonicida, particularly in relation to its piscine host spectrum and the geographic distribution of these hosts. Abstract : Sub-lineages of the fish-pathogenic bacterium Aeromonas salmonicida display specific host preferences.